A micro-macro economic analysis of pension auto-enrolment options - Maxime Bercholz; Adele Bergin; Tim Callan; Abian Garcia Rodriguez; Claire Keane (The Economic and Social Research Institute (ESRI), 2019)
In the context of reducing greenhouse gas emissions in the residential sector, fuel switching from coal and oil to natural gas is considered as a policy option. The paper considers fuel choice decisions among households within 30 metres of the Irish natural gas network. Consistent with earlier research a range of building attributes and household characteristics are associated with fuel choice for household space heating. Additionally, there are substantial distance decay effcts with respect to gas network connection within relatively close proximity to the network, meaning that properties further distant from the gas network are less likely to be gas customers. The distance decay effects are likely attributed to network connection fees, which are proportional to the connection distance. The paper simulates the impact of eliminating distance decay effects, i.e. the marginal connection cost associated with distance is set to zero, and examines emission and expenditure impacts across socioeconomic groups. The analysis finds that up to 13% of unconnected properties are likely to respond to such an incentive, yielding a 3.9% reduction in greenhouse gas emissions and a 1.5% reduction in fuel expenditure relative to pre-policy levels of unconnected households within the study. Expenditure and emission impacts differ across socio-economic groups with the largest reductions expected to occur among semi-skilled/unskilled households, which are frequently among the least affluent households. Though counter-intuitive, greenhouse gas emissions from the residential sector could be reduced by incentivising connections to the natural gas network.
Keywords: 330